Activation and Inhibition of the NLRP3 Inflammasome by RNA Viruses - Choudhury SM; Ma X; Abdullah SW; Zheng H (Dove Medical Press, 2021)
SK Mohiuddin Choudhury,* XuSheng Ma,* Sahibzada Waheed Abdullah, HaiXue Zheng State Key Laboratory of Veterinary Etiological Biology, National Foot and Mouth Disease Reference Laboratory, Key Laboratory of Animal Virology of Ministry of Agriculture, Lanzhou Veterinary Research Institute, Chinese Academy of Agricultural Sciences, Lanzhou, 730046, Gansu, People’s Republic of China*These authors contributed equally to this workCorrespondence: HaiXue ZhengState Key Laboratory of Veterinary Etiological Biology, National Foot and Mouth Disease Reference Laboratory, Key Laboratory of Animal Virology of Ministry of Agriculture, Lanzhou Veterinary Research Institute, Chinese Academy of Agricultural Sciences, Lanzhou, 730046, Gansu, People’s Republic of ChinaTel +86-931-8342086Email haixuezheng@163.comAbstract: Inflammation refers to the response of the immune system to viral, bacterial, and fungal infections, or other foreign particles in the body, which can involve the production of a wide array of soluble inflammatory mediators. It is important for the development of many RNA virus-infected diseases. The primary factors through which the infection becomes inflammation involve inflammasome. Inflammasomes are proteins complex that the activation is responsive to specific pathogens, host cell damage, and other environmental stimuli. Inflammasomes bring about the maturation of various pro-inflammatory cytokines such as IL-18 and IL-1β in order to mediate the innate immune defense mechanisms. Many RNA viruses and their components, such as encephalomyocarditis virus (EMCV) 2B viroporin, the viral RNA of hepatitis C virus, the influenza virus M2 viroporin, the respiratory syncytial virus (RSV) small hydrophobic (SH) viroporin, and the human rhinovirus (HRV) 2B viroporin can activate the Nod-like receptor (NLR) family pyrin domain-containing 3 (NLRP3) inflammasome to influence the inflammatory response. On the other hand, several viruses use virus-encoded proteins to suppress inflammation activation, such as the influenza virus NS1 protein and the measles virus (MV) V protein. In this review, we summarize how RNA virus infection leads to the activation or inhibition of the NLRP3 inflammasome.Keywords: inflammation, NLRP3 inflammasome, RNA viruses, activation and inhibition of NLRP3, viral protein and genome